The dynamics of the religious plurality in Mexico - Masferrer Kan, Elio (2014)
One of the main characteristics of the Mexican religious fi eld is its reformulation and diversifi cation. This paper will try to evaluate the conformation of its different sectors and confront it with the “offi cial” fi gures which distort the reality of this fi eld. The paper will try to contribute to the reconstruction of the existing information, attempting to regionalize and adjust the information, with the introduction of new parameters and indicators. The conceptual starting point is that the general census of the population does not refl ect the reality of the religious fi eld and that the reconstruction of the information should be based on the dynamics of the rites of passage, the conversion to new religious proposals, the strengthening of the nonbeliever sector and the consolidation of the Evangelical, Pentecostal and Parachristian (Mormons, Jehova Witnesses and Adventists) proposals. The results of the investigationpresented point to a quantitative and qualitative analysis of the existing information.